Legal Review of Islam on the Prohibition of Marriage Contracts between Eid al-Fitr and Eid al-Adha - Rifal, Muh; Muchtar, M. Ilham (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
This study examines the local tradition that prohibits the performance of marriage contracts between the two Islamic holidays (Eid al-Fitr and Eid al-Adha), as still practiced by some communities, such as those in Gentungang Village, West Bajeng Subdistrict, Gowa Regency, South Sulawesi. This tradition is an interesting phenomenon because it contradicts the fundamental principles of Islamic law, which does not specify a specific timeframe for conducting marriages. This study aims to assess the compatibility of this tradition with Islamic legal provisions through a legal-normative approach based on the Quran, hadith, fiqh principles, and the concept of 'urf (custom). The results of the study indicate that the tradition of prohibiting marriage between the two holidays falls under the categories of 'urf fi'li and 'urf khas, but does not meet the criteria for 'urf shahih because it contradicts Islamic legal evidence, such as the hadith encouraging marriage in the month of Shawwal. Additionally, this prohibition causes harm by restricting individuals' rights to marry, which, in principle, must be eliminated in Islamic law. Therefore, this study recommends legal education for the public to clarify understanding and promote the reconstruction of moderate and contextual religious values. The integration of religious norms and local culture remains important, but it must be done without violating the principles of Sharia.